Recent Patents in Cartilage Regeneration - Labusca, Luminita; Greiser, Udo; Nacu, Viorel; Zugun-Eloae, Florin; Mashayekhi, Kaveh (Recent Patents on Regenerative Medicine, 2014)
The limited capability of articular cartilage to heal after injury and the worldwide increase in the burden of diseases related to osteoarthritis, are prompting numerous efforts in developing novel treatments. Methods of grafting, promoting tissue repair or regenerative medicine strategies are in different stages of investigation. However, in the last decades, inadequate few novel therapies have made their way to the clinic gaining limited acceptance. Some of the reasons of the relative lack of progress are the insufficient quality and stability of the repair tissue and the lack of serious evidence based medicine information to support the use and reimbursement of new procedures. This paper introduces the most recent patents which relate to cartilage regeneration. Grafting procedures and their conceptual development, regenerative medicine strategies as well as drug, physical and food supplements based methods are listed. Main issues encountered with every intervention type and the way new methods are addressing them, are also discussed.
Keywords: patents